Pengaruh Kecerdasan Emosional terhadap Sikap Sosial Siswa di MTs Miftahul Ulum - Zainab, Siti; Maula, Istul; Maulana, Mohammad Thoyib; Prasetiya, Benny (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
The urgency of this study is based on the phenomenon of declining social attitudes among students in school environments, such as low levels of empathy, cooperation, and social responsibility, as well as the limited number of empirical studies examining the relationship between emotional intelligence and social attitudes in the context of Islamic junior high school education. This study aims to examine the effect of emotional intelligence on students’ social attitudes at MTs Miftahul Ulum and to analyze the extent of emotional intelligence’s contribution to the development of students’ social attitudes. This study employed a quantitative approach with a correlational research design. The research population consisted of all 120 students of MTs Miftahul Ulum, with a sample of 60 students selected using a simple random sampling technique. Data were collected through Likert-scale questionnaires measuring emotional intelligence and students’ social attitudes. Data analysis was conducted using simple linear regression assisted by SPSS, after meeting the required assumption tests. The results indicate that emotional intelligence has a significant and positive effect on students’ social attitudes, with a significance value of 0.000. Furthermore, the coefficient of determination shows that emotional intelligence contributes 69.6% to the variation in students’ social attitudes. These findings confirm that emotional intelligence plays a strategic role in shaping students’ social attitudes in the madrasah environment.ABSTRAKUrgensi penelitian ini didasarkan pada fenomena melemahnya sikap sosial siswa di lingkungan sekolah, seperti rendahnya empati, kerja sama, dan tanggung jawab sosial, serta masih terbatasnya kajian empiris yang mengkaji hubungan kecerdasan emosional dan sikap sosial dalam konteks pendidikan madrasah tsanawiyah. Penelitian ini bertujuan untuk menguji pengaruh kecerdasan emosional terhadap sikap sosial siswa di MTs Miftahul Ulum serta menganalisis besarnya kontribusi kecerdasan emosional dalam membentuk sikap sosial peserta didik. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian korelasional. Populasi penelitian adalah seluruh siswa MTs Miftahul Ulum yang berjumlah 120 siswa, dengan sampel sebanyak 60 siswa yang dipilih menggunakan teknik simple random sampling. Pengumpulan data dilakukan melalui kuesioner berbasis skala Likert yang mengukur kecerdasan emosional dan sikap sosial siswa. Analisis data dilakukan menggunakan regresi linear sederhana berbantuan SPSS, setelah memenuhi uji prasyarat analisis. Hasil penelitian menunjukkan bahwa kecerdasan emosional berpengaruh signifikan dan positif terhadap sikap sosial siswa dengan nilai signifikansi 0,000. Selain itu, hasil uji koefisien determinasi menunjukkan bahwa kecerdasan emosional memberikan kontribusi sebesar 69,6% terhadap variasi sikap sosial siswa. Temuan ini menegaskan bahwa kecerdasan emosional memiliki peran strategis dalam pembentukan sikap sosial peserta didik di lingkungan madrasah.